Kecerdasan Emosional Guru Dalam Membina Moralitas Peserta Didik - Muh. Habibulloh; Binti Maunah (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2015)
The research in this thesis is motivated by moral aspect rather than overlooking learners, particularlyÂ learners who are experiencing puberty, when their curiosity raging-nggebu with things that are foreign toÂ them. Technology is the most dominant factor in supporting their curiosity. For example, technology deliversÂ everything instantly, software that enables google search of all knowledge, knowledge that can be both positiveÂ and negative. Subsequently, this fact affects the young who employ such technology improperly, especiallyÂ those who are students. The rise of the porn video that has spread in cyberspace make this negative impactÂ worse to those who are still studying. Thus, this situation requires teachers who are emotionally intelligent andÂ have good morality in order to produce reliable output. Teachers who become educators at both institutionsÂ already have experience of EQ tests in collaboration with other universities psychiatrist. Emotional intelligenceÂ determines our potential to learn the skills - practical skills based on five elements: self-awareness, motivation,Â self-regulation, empathy and skills in developing relationships with others. This is associated with emotionalÂ intelligence as a teacher educator, who have the ability to recognize emotions, self-control, self-motivation,Â empathy and fostering hunbungan to provide a forum for students to pay more attention to their behavior.Â Students will indirectly follow what the teacher do.